Genetic and non-genetic mechanisms of inflammation may promote transformation in leukemia - Vyas, P (Elsevier, 2022)
Non-genetic mechanisms of transformation are still relatively understudied and poorly understood. In this issue of Cell Stem Cell, Muto et al. provide preclinical evidence that loss of TRAF6 expression promotes transformation through a MYC-dependent mechanism that may be modulated by environmental inflammatory signals.